Challenges in Recruiting, Retaining and Promoting Racially and Ethnically Diverse Faculty - Kaplan, Samantha E. (J Natl Med Assoc, 2017)
BACKGROUND: Despite individual and institutional awareness of the inequity in retention, promotion and leadership of racially and ethnically underrepresented minority faculty in academic medicine, the number of such faculty remains unacceptably low. The authors explored challenges to the recruitment, retention and promotion of underrepresented faculty among a sample of leaders at academic medical centers. METHODS: Semi-structured interviews were conducted from 2011–2012 with 44 senior faculty leaders, predominantly members of the Group on Diversity and Inclusion (GDI) and/or the Group on Women in Medical Sciences (GWIMS), at the 24 randomly selected medical schools of the National Faculty Survey of 1995. All institutions were in the continental United States and balanced across public/private status and geographic region. Interviews were audio-taped, transcribed, and organized into content areas before conducting inductive thematic analysis. Themes expressed by multiple informants were studied for patterns of association. RESULTS: The climate for underrepresented minority faculty was described as neutral to positive. Three consistent themes were identified regarding the challenges to recruitment, retention and promotion of underrepresented faculty: 1) the continued lack of a critical mass of minority faculty; 2) the need for coordinated programmatic efforts and resources necessary to address retention and promotion; and 3) the need for a senior leader champion. CONCLUSION: Despite a generally positive climate, the lack of a critical mass remains a barrier to recruitment of racially and ethnically underrepresented faculty in medicine. Programs and resources committed to retention and promotion of minority faculty and institutional leadership are critical to building a diverse faculty.